PENGARUH LOAN TO DEPOSIT RATIO (LDR), NONPERFORMING LOAN (NPL) DAN NET INTEREST MARGIN (NIM) TERHADAP PERTUMBUHAN PINJAMAN USAHA KECIL DAN MENENGAH BANK PEMBANGUNAN DAERAH - ISNURHADI .; IRINA KARTIKA; H M A RASYID UMRIE (Program Studi Magister Manajemen FE Unsri, 2015)
This study is aimed at determining the effect of liquidity ratio (LDR), asset quality ratio (NPL) and the net interest margin (NIM) to growth of Small and Medium Enterprises (SME) loans from local banks (BPD). The study uses purposive sampling method in determining the sample. Out of 26 local banks in Indonesia, six are selected as samples for this study. Multiple regression used to analize the data shows that LDR and NIM have a positive effect on the growth of SME loans from local bank while NPL has a negative effect on the growth. Simultaneous analysis shows combined effect of LDR, NPL and NIM on the growth of SME loans is significant. The coefficient of determination (R2) of relationship between the three variables on the growth of SME loans from BPD is 0,298. It means that the LDR, NPL and NIM have about 30% influences on the growth of SME loans.